2016
DOI: 10.1515/hf-2015-0165
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state 29Si NMR and FTIR analyses of lignin-silica coprecipitates

Abstract: When agricultural residues are processed to ethanol, lignin and silica are some of the main byproducts. Separation of these two products is difficult and the chemical interactions between lignin and silica are not well described. In the present study, the effect of lignin-silica complexing has been investigated by characterizing lignin and silica coprecipitates by FTIR and solid state NMR. Silica particles were coprecipitated with three different lignins, three lignin model compounds, and two silanes represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The SONE allowed us to analyse organic matter that was intimately associated with the silica (Figure 4 and Figure S1). Our results indicated that the Si atoms are coordinated to oxygen, similarly to silica gel and opal, in agreement with analyses of in planta silica (Yoshida et al, 1959;Casey et al, 2004) and in vitro precipitation with lignin (Cabrera et al, 2016;Soukup et al, 2019). We cannot exclude the existence of Si-O-C bonds as detected by X-ray photoelectron spectroscopy in cell walls extracted from rice cell suspension (He et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…The SONE allowed us to analyse organic matter that was intimately associated with the silica (Figure 4 and Figure S1). Our results indicated that the Si atoms are coordinated to oxygen, similarly to silica gel and opal, in agreement with analyses of in planta silica (Yoshida et al, 1959;Casey et al, 2004) and in vitro precipitation with lignin (Cabrera et al, 2016;Soukup et al, 2019). We cannot exclude the existence of Si-O-C bonds as detected by X-ray photoelectron spectroscopy in cell walls extracted from rice cell suspension (He et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Lignin associates with polysaccharides, especially hemicellulose, via covalent bonds to form lignin-carbohydrate complexes. Likewise, silica is hypothesized to have interaction with cellulose and lignin 11 , 12 . The recalcitrant structure of lignocellulosic biomass inhibits bio-refineries such as the fermentation of cellulose for bioethanol, conversion of lignin into value-added chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Results from material science studies show that SiO 2 can covalently bind to lignin (e.g. Strzemiecka et al, 2016) an idea that is strengthened by NMR studies on lignin-silica co-precipitates (Cabrera et al, 2016). The ensuing physical barrier will limit both ion and water permeability, forcing a relatively large proportion to move via the symplast where flux control is far greater.…”
Section: Ion Transportmentioning
confidence: 99%